Psychotic manifesto as a symbolic safe space - Romaniv, Olexandr; Pohoriliak, Kateryna; Nad, Beata (Psychosomatic Medicine and General Practice, 2018)
The clinical case reflects the manifestation of psychosis in a patient of 22 years who turned to a psychiatrist, accompanied by his parents. He has always shown remarkable success in his studies and professional activities. The development of psychotic symptoms significantly reduced his overall activity and quality of life. From the anamnesis, it became known that he always preferred to be lonely than in the company of peers. He communicated a lot on the Internet. At home was often under pressure from his parents. He had a younger brother who annoyed him. The onset of the illness was marked by the bright visions he had seen throughout the day. Before the onset of the illness, he always believed in the underworld and had the feeling that he should die, because of this he was afraid to look in the mirror. He felt that his thoughts could be read by his surroundings. Psychiatric status: tension, anxiety and alertness, low mood, sadness, pessimism. Emotionally labile, demonstrated affective outbursts during the conversation. Сlinical interviewing was complicated by the disorganization of mental processes. Verbal cognitive processes during the interview were reduced. For psychodiagnostic examination was used MINI (international neuropsychiatric interview), FPI (Freiburg Personality Questionnaire), Thematic apperception test, SCI-PANSS (Positive and negative syndrome scale), ADI-R (Autism Diagnostic interview), ADOS (Autism Diagnostic Observation Schedule). At the same time, the patient fulfills the criteria for several psychiatric disorders: a major depressive episode, social and generalized anxiety disorder, posttraumatic stress disorder, suicidal thoughts, intentions, attempts in the past, indicating high current suicidality, current psychotic disorder. Propensities: limited social and communicative skills, poor social experience, resistance to behavioral patterns, which in the patient were clinical manifestations of ASD and demanding mothers. The growing social expectations, which in a certain period of life of the patient was unable to respond, became provocative events that triggered the development of psychotic symptoms. On the background of a successful treatment, the patient began attending sessions at a psychotherapist with a client-focused psychotherapy direction.